Perancangan Lakon Ramabargawa: Respon Estetik Kisah-Kisah Ramabargawa - Fani Rickyansyah (Institut Seni Indonesia Yogyakarta, 2019)
The design of the Ramabargawa play is a realization from a perspective on reading Ramabargawa stories that have been known by the community. In addition to offering a perspective, this work also aims as a medium to communicate the idea of a harmonious family. Wolfgang Iser’s Aesthetic Response Theory is used as a frame of mind. The texts of the Ramabargawa story known to the public as the text of the sender were responded to by the recipient of the work, then realized in the design of the Ramabargawa play. Ramabargawa’s play is a response to the Ramabargawa story that is considered common by the community. This play is packed in solid shows with a duration of one and a half hours. This Ramabargawa play is presented in the style of Pakeliran Yogyakarta that is developing today. New working idioms that make pakeliran offeringsare more interesting, weighty, and in accordance with the development of puppetry today displayed in the show. This is intended so that the Yogyakarta-style shadow puppet show continues to be sustainable but continues to grow with a variety of new innovations.Perancangan lakon Ramabargawa merupakan realisasi dari sebuah sudut pandang atas pembacaan kisah-kisah Ramabargawa yang telah dikenal oleh masyarakat. Selain menawarkan sebuah sudut pandang, karya ini juga bertujuan sebagai media mengkomunikasikan gagasan tentang keluarga harmonis. Teori Respon Estetik Wolfgang Iser dipakai sebagai kerangka berpikir. Teks-teks kisah Ramabargawa yang telah dikenal masyarakat sebagai teks pengirim direspon oleh pengkarya sebagaipenerima, lalu direalisasikan dalam perancangan lakon Ramabargawa. Lakon Ramabargawa merupakan respon atas cerita Ramabargawa yang dianggap lazim oleh masyarakat. Lakon ini dikemas dalam pertunjukan padat dengan durasi waktu satu setengah jam. Lakon Ramabargawa ini disajikan dengan gaya Pakeliran Yogyakarta yang berkembang dewasa ini. Idiom-idiom garap baru yang membuat sajian pakeliran lebih menarik, berbobot, dan sesuai dengan perkembangan pedalangan zaman sekarang ditampilkan dalam pertunjukan. Hal tersebut dimaksudkan agar pertunjukan wayang kulit purwa gaya Yogyakarta tetap lestari namun terusberkembang dengan berbagai inovasi baru.